Combinação de óxidos mistos aplicados como catalisadores na reação de reforma seca do metano para produção de gás de síntese - Ramon, Adriana Paula (2020)
Dry reforming of methane (DRM) is a promising process in synthetic gas generation with a low H2/CO ratio. The generation of syngas is of great industrial interest in a number of processes, in particular in the production of liquid fuels via Fischer-Tropsch synthesis. The main problems in DRM are the large formation of carbon deposition over the catalyst. In an attempt to overcome this problem, different supports consisting of mixed oxides with stable structure such as pyrochlore and perovskite types have been developed. In this work we studied the effect of several parameters in the proposed syntheses, as well as the comparison between the modified Pechini, sol-gel, coprecipitation and hydrothermal methods. Besides that, we studied the effect of metal loading on activity in the DRM over the catalysts synthesized by sol-gel method. These catalysts were characterized by several techniques and some were tested at the DRM at temperatures between 600 to 900 °C, in addition they were tested at short-term stability at 600 and/or 850 °C. X-ray diffraction analysis showed the formation of pyrochlore La2Ce2O7-δ and perovskite LaNiO3 phases in all four synthesis methods, moreover, in the samples synthesized by coprecipitation and hydrothermal methods NiO was also present. In addition to these phases, the principal component analysis applied to the X-ray absorption near edge structure (XANES) during temperature programmed reduction data showed the presence of defect perovskite La2Ni2O5. The catalytic tests showed that regardless of the synthesis method and nickel loading, all catalysts were stable during the short-term stability test at 600 and/or 850 °C. The material synthesized by hydrothermal method showed the highest conversions and yields at temperatures from 600 to 900 °C. In addition, at 850°C the conversion was ~90% and lead to a preferential stoichiometric reaction pathway, which is ideal for the DRM reaction. The better performance in this material was related to the greater interaction between nickel and cerium. Further, the H2/CO ratio varied from 0,5 to 0,9, depending on the material and the reaction conditions. Moreover, the reaction mechanism proposed in these materials at 600 °C takes into account the intermediates CHx and OH, which were observed in APXPS analysis. Through the APXPS and thermogravimetric analyzes after stability test, it was revealed no significant carbon deposition in the samples (<2% wt).